La coltre del silenzio: timori e speranze (Stato, Chiese e pluralismo confessionale, 2023)
The blanket of silence: fears and hopesABSTRACT: The silence of the parties governing the country and those belonging to the opposition persists. Their political orientation on the 'ecclesiastical matters' is yet to be shared, as well as their position on the need for a more general law on religious freedom. The new conservative government keeps silent. There are signs of a possible failure to comply with the pluralistic principle, which is the cornerstone of the secular nature of the State. Between hopes and fears, the latter could prevail.